2017
DOI: 10.3233/jpd-161036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Prodromal Parkinson’s Disease as Defined by MDS Research Criteria among Elderly Patients Undergoing Colonoscopy

Abstract: Our findings suggest, that the prevalence of prodromal PD in patients undergoing diagnostic colonoscopies may be higher compared to the general elderly population, although this should be confirmed in further studies including also matched controls not undergoing colonoscopy. The real prevalence of prodromal PD in this cohort will have to be confirmed in longitudinal follow-up. Patients undergoing diagnostic colonoscopies may be good candidates for multistep screening and inclusion in prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Overall, we collected data for the vast majority of markers: 13 of 17 (8 of 10 prodromal markers). Furthermore, according to MDS recommendations and recent studies, pPD probability may be calculated using available markers in each cohort, keeping in mind that it may be underestimated if the number of markers is limited. Yet, pPD probability in our study was quite similar to that found in other cohort of older adults …”
Section: Discussionmentioning
confidence: 99%
“…Overall, we collected data for the vast majority of markers: 13 of 17 (8 of 10 prodromal markers). Furthermore, according to MDS recommendations and recent studies, pPD probability may be calculated using available markers in each cohort, keeping in mind that it may be underestimated if the number of markers is limited. Yet, pPD probability in our study was quite similar to that found in other cohort of older adults …”
Section: Discussionmentioning
confidence: 99%
“…Such scores on the UPDRS 2 years prior showed a very high specificity of 97% and sensitivity of 94% with overall area under curve (AUC) of 0.99 for conversion to parkinsonism ( 42 ),. These cutoffs, however, still need to be validated in more prospective trials, as up to 30% of elderly patients may score >6 points on the MDS-UPDRS part III without including the action tremor items ( 57 ).…”
Section: Diagnostic Accuracy Of Clinical Measures For Predicting Convmentioning
confidence: 99%
“…On the whole, we collected data for the vast majority of MDS markers: 13 of 17 (8 of 10 prodromal markers). As MDS and recent studies have suggested, pPD probability may be calculated using available markers in each cohort, keeping in mind that it may be underestimated if the number of markers is limited.…”
Section: Methodsmentioning
confidence: 99%